1978
DOI: 10.1159/000158176
|View full text |Cite
|
Sign up to set email alerts
|

Venous Changes in Renal Hypertensive Rats: The Role of Humoral Factors

Abstract: In order to investigate the role of circulating humoral substances in the pathogenesis of venous changes in experimental hypertension, an attempt was made to induce venous changes in rats in parabiosis with two-kidney Goldblatt hypertensive rats. Sham-operated normotensive rats in parabiosis were used as controls. Venous pressure-volume curves were obtained in the pump perfused vascular beds of the lower body of rats by recording the femoral vein pressure rise during rapid infusion of fluid into the inferior v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This study, although in part confirmatory of previous in vivo experiments, 5 used in vitro techniques, therefore, its findings have to be interpreted with caution. Several studies have indicated that isolated vascular smooth muscle cells in culture must first "dedifferentiate" to morphologically resemble fibroblasts before proliferation will occur.…”
Section: Discussionsupporting
confidence: 73%
“…This study, although in part confirmatory of previous in vivo experiments, 5 used in vitro techniques, therefore, its findings have to be interpreted with caution. Several studies have indicated that isolated vascular smooth muscle cells in culture must first "dedifferentiate" to morphologically resemble fibroblasts before proliferation will occur.…”
Section: Discussionsupporting
confidence: 73%
“…1,6,7 Older studies also implicate an unknown humoral mechanism that operates in some models of experimental hypertension. 8 The endothelium-derived peptide endothelin (ET)-1 is a potent venoconstrictor in most vascular beds. 9 Changes in endogenous ET-1 formation consistent with a role for the peptide in venomotor adjustments to volume stimuli have been measured in humans.…”
mentioning
confidence: 99%
“…It is unclear whether the increase in medial thickness is specific for renal hypertension; whereas Sudhir et al [9] did not find a difference in medial thickness of superficial forearm veins between subjects with essential hyperten sion and normotensive controls, Simon et al [10] ob served an increase in water and hexosamine content of the venous wall of hypertensive humans [10], Furthermore, an increase in medial thickness was ob served in hypertensive rats and dogs [11][12][13][14][15], Greenberg et al [11] observed an increase in mucopolysaccharides and glycoproteins in combination with medial smooth muscle cell hyperplasia in veins of spontaneously hyper tensive rats.…”
Section: Discussionmentioning
confidence: 99%